2. Diagnosis and Classification of Diabetes: Standards of Care in Diabetes—2024 - ElSayed, Nuha A.; Aleppo, Grazia; Bannuru, Raveendhara R.; Bruemmer, Dennis; Collins, Billy S.; Ekhlaspour, Laya; Gaglia, Jason L.; Hilliard, Marisa E.; Johnson, Eric L.; Khunti, Kamlesh; Lingvay, Ildiko; Matfin, Glenn; et al. (Diabetes care, 2024)
The American Diabetes Association (ADA) “Standards of Care in Diabetes” includes the ADA’s current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, an interprofessional expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements, and reports, as well as the evidence-grading system for ADA’s clinical practice recommendations and a full list of Professional Practice Committee members, please refer to Introduction and Methodology. Readers who wish to comment on the Standards of Care are invited to do so at professional.diabetes.org/SOC.